Woody Vegetation Types and floristic composition in the Unesco Global Geopark Mixteca Alta, Oaxaca - Ramírez Santiago, Rosario; Orozco-Ramírez, Quetzalcóatl; Clark Tapia, Ricardo; Cruz Ramírez, Miguel Ángel (Instituto de Ecología, A.C., 2021)
We describe land cover and floristic composition of woody vegetation in the Mixteca Alta Geopark (GMA), in the state of Oaxaca. Land cover types were identified by a visual classification on a satellite imagery from Google Earth (2016). Land cover types were verified on the ground doing fieldtrips. We identified nine land cover types. Four of them were woody vegetation, which were sampled to determine their floristic composition. We set 70 temporal sampling sites of 500 m2 each. We counted and measured trees and bushes. In total 91 species were recorded from 55 genus and 31 families. Floristic composition is like other temperate zones in Mexico but, richness in our study site is lower. However, oak forest and oak and pine forest are richer in species than xerophytic scrub and scrub with juniper. The composition and structure show that the vegetation is secondary, it means that it has regrown by secondary succession processes. Currently the GMA area forest cover is growing, and local communities have had a role in this process.